Development and pilot test of a physician-focused cancer clinical trials communication training intervention - Susan Eggly; Mark Manning; Nicole Senft; Tanina Foster Moore; Terrance L. Albrecht; Louis A. Penner; Elisabeth Heath; Michael A. Carducci; Dina G. Lansey; Lauren M. Hamel (Elsevier, 2022)
Objective: We describe the development and pilot test of a physician-focused, web-based training module designed to improve physician communication related to clinical trials in a diverse cancer patient population. Methods: Researchers and stakeholders developed the training module, which included a video explaining patient-centered communication strategies for discussing trials, and re-enactments of actual clinical interactions. For the pilot test, the module was provided to physician participants in the Partnering Around Cancer Clinical Trials (PACCT) trial at two major urban cancer centers. Questionnaires assessed change in beliefs, behavioral attitudes, knowledge and comfort; and perceptions of the module. Results: Nineteen physicians participated in the pilot test. Most were experienced in discussing trials. Assessments of change were mixed regarding beliefs; they showed marginal improvement in attitudes, and significant improvement in knowledge, but no change in comfort. Feedback on the module was favorable. Conclusions: This stakeholder-developed physician communication training module was acceptable and effective, albeit in this small and highly-experienced physician sample. Future research should determine its effectiveness on communication in clinical settings. Innovation: This is the first physician training module to focus on communicating about clinical trials in a diverse patient population. It offers a web-based format and re-enactments of naturally-occurring clinical interactions.Trial Registration Number: NCT02906241